Incidence and determinants of graft failure and death with functioning graft after re-transplantation - Coens, Ferran; Reynders, Dries; Goetghebeur, Els; Tieken, Ineke; Vogelaar, Serge; Krupka, Kai; Raes, Ann; Claas, Frans; Tönshoff, Burkhard; Prytuła, Agnieszka (Pediatric nephrology, 2025)
Recent reports on allograft survival after repeat kidney transplantation (KTx) and the incidence and determinants of graft failure (GF) are lacking.
Gesehen am 11.12.2025